2015
DOI: 10.1111/1346-8138.12876
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 levels and bone mineral density in patients with psoriasis and/or psoriatic arthritis

Abstract: Limited data are available on the vitamin D 3 status and bone mineral density (BMD) of patients with psoriasis or with psoriatic arthritis. Our study intended to explore possible correlations between vitamin D status and BMD, as well as among these parameters and the features of the underlying disorder. Seventy-two patients with psoriasis/ or psoriatic arthritis (female : male ratio, 40:32; mean age, 58.5 AE 11.6 years; mean duration of follow up, 142.7 AE 147.7 months) participated in the study. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
7
23
0
3
Order By: Relevance
“…Therefore, low levels of vitamin D are negatively associated with markers of inflammatory activation (C-reactive protein, CRP) and obesity [35]. Moreover, other studies showed that serum vitamin D levels were also reduced in patients with psoriatic arthritis and being inversely linked to disease activity [46, 47] . …”
Section: The Dermatologist’s Point Of Viewmentioning
confidence: 99%
“…Therefore, low levels of vitamin D are negatively associated with markers of inflammatory activation (C-reactive protein, CRP) and obesity [35]. Moreover, other studies showed that serum vitamin D levels were also reduced in patients with psoriatic arthritis and being inversely linked to disease activity [46, 47] . …”
Section: The Dermatologist’s Point Of Viewmentioning
confidence: 99%
“…In this context, it is intriguing that dipeptidyl peptidase-4 inhibitors, a new class of antidiabetic agents, have been shown to improve skin symptoms in some psoriasis patients (62). Because topical vitamin D3 application is effective in treating psoriasis (63), the vitamin D3 level and bone mineral density have been assessed (64, 65). In those studies, the serum level of vitamin 25(OH)D3 was inversely correlated with the severity of psoriasis (64).…”
Section: Comorbidity With Metabolic Syndromementioning
confidence: 99%
“…Because topical vitamin D3 application is effective in treating psoriasis (63), the vitamin D3 level and bone mineral density have been assessed (64, 65). In those studies, the serum level of vitamin 25(OH)D3 was inversely correlated with the severity of psoriasis (64). Patients with a low bone mineral density showed a statistically significant longer average duration of psoriasis than those with better bone density (65).…”
Section: Comorbidity With Metabolic Syndromementioning
confidence: 99%
“…В то же вре-мя в работе G. Kincse и соавт. [13] выявлена достоверно большая частота снижения МПК среди пациентов с ПсА и псориазом по сравнению со здоровыми женщинами и мужчинами в возрасте старше 50 лет (63,8; 32,3 и 23,6% соответственно). В исследовании B. Frediani и соавт.…”
unclassified
“…Так, в работе G. Kincse и соавт. [13] показана достоверная ассоциация недостаточности витамина D с высокой активностью ПсА, в то же время в работе B. Baskan и соавт. [22] корреляция уровня вита-мина D с качеством жизни (PSAQoL), числом болезнен-ных суставов, показателями HAQ-S, MASES и BASDAI у больных ПсА была статистически незначимой.…”
unclassified